Letter (copy) : "Volunteers" for Spain - Citrine, Walter, 1887-1983
012a-0126-001 International WMC/WJB/AC/422 29th March , 1938. Mr. H. Schliestedt, C/o Mr. W. Schevenels, International Federation of Trade Unions, 9, avenue d'Orsay, PARIS VIIe. Dear Comrade Schliestedt, "VOLUNTEERS" FOR SPAIN. Your letter of 22nd instant duly reached me, containing details about "volunteers" for Spain etc. I am very much obliged to you for the information. I will convey it to my colleagues before coming to a decision as to the proper course to take, and in regard to which there will be no unnecessary delay. Yours faithfully, General Secretary. 292/946/12a/126